2010
DOI: 10.1001/archgenpsychiatry.2010.125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acamprosate on Magnetic Resonance Spectroscopy Measures of Central Glutamate in Detoxified Alcohol-Dependent Individuals

Abstract: Context Acamprosate is approved for treatment of alcoholism, but its mechanism of action remains unclear. Animal studies suggest that a persistent hyperglutamatergic state contributes to the pathophysiology of alcoholism, and that acamprosate may exert its actions by intervening in this process. Human translation of these findings is lacking. Objective To examine whether acamprosate modulates indices of central glutamate levels in recently abstinent alcohol dependent patients, as measured by proton nuclear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 47 publications
5
101
1
Order By: Relevance
“…As noted above, clinical MRS studies have reported increased glutamate activity in anterior cingulate and NAc in abstinent human alcoholics compared with age-and sexmatched healthy controls (Bauer et al, 2013;Hermann et al, 2012). In another MRS study, acamprosate was found to reduce glutamate levels in anterior cingulate several weeks after abstinence (Umhau et al, 2010). Acamprosate is an FDA-approved medication for alcohol dependence that is thought to alter central glutamate neurotransmission, although its mechanism of action is not fully understood and reports on its clinical efficacy in treating alcohol dependence have been mixed (Berger et al, 2013;Mann et al, 2012;Mason and Lehert, 2012;Mann et al 2012;Yahn et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…As noted above, clinical MRS studies have reported increased glutamate activity in anterior cingulate and NAc in abstinent human alcoholics compared with age-and sexmatched healthy controls (Bauer et al, 2013;Hermann et al, 2012). In another MRS study, acamprosate was found to reduce glutamate levels in anterior cingulate several weeks after abstinence (Umhau et al, 2010). Acamprosate is an FDA-approved medication for alcohol dependence that is thought to alter central glutamate neurotransmission, although its mechanism of action is not fully understood and reports on its clinical efficacy in treating alcohol dependence have been mixed (Berger et al, 2013;Mann et al, 2012;Mason and Lehert, 2012;Mann et al 2012;Yahn et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…Both alcoholdependent rats and alcohol-dependent patients showed increased glutamate levels during acute alcohol withdrawal in corresponding prefrontocortical regions (Hermann et al, 2012). Another MRS study indicated that glutamate levels in the anterior cingulate cortex of alcohol-dependent patients continue to increase over 3 weeks following cessation of alcohol use and that the approved alcoholism medication acamprosate prevents this increase (Umhau et al, 2010). Seemingly in agreement with these observations, mGluR2/3 agonists can affect alcohol-related behaviors.…”
Section: Introductionmentioning
confidence: 68%
“…Acamprosate dampens hyperglutamatergic activity in excessively ethanol drinking mice, thereby reducing alcohol intake (Mann et al 2008;Spanagel et al, 2005). In a recent double-blind, placebo-controlled study, which applied magnetic resonance spectroscopy acamprosate also reduced glutamate levels in the brains of detoxified alcoholdependent patients (Umhau et al, 2010). Although the effects of acamprosate on glutamate levels are well documented, the molecular mode of action of this drug and the putative interaction between acamprosate and glutamate receptors remains unclear.…”
Section: Introductionmentioning
confidence: 99%